The politics of war memory in Japan : progressive civil society groups and contestation of memory of the Asia-Pacific war - Szczepanska, Kamila (New York : Routledge/Taylor & Francis Group, 2014)
'Since the 1990s, questions of Japanese wartime conduct, apologies for aggression, and compensation to former victims of the country's imperial policies, have been brought to the fore of national and regional politics. The state is undoubtedly the most important actor in the process of memory production and along with conservative legislators and the grass-root revisionist movement there has been a consistent failure to acknowledge responsibility for Japan's wartime past. However, to fully comprehend war memory in Japan, due attention must be paid to competing discourses that demand an alternative view, and only then can the true complexity of Japanese war memory and attitudes towards the legacies of the Asia-Pacific war be understood. The Politics of War Memory in Japan examines the involvement of five civil society actors in the struggle over remembering and addressing the wartime past in Japan today. In studying progressive war memory activists, it quickly becomes clear that the apologia by conservative politicians cannot be treated as representative of the opinion of the majority of the Japanese public. Indeed, this book seeks to remedy the disparity between studies devoted to the official level of addressing the'history issue' and the grass-root historical revisionist movement on the one side, and progressive activism on the other. Furthermore, it contributes to scholarly debates on the state of civil society in Japan, challenging the characterisation of Japanese civil society as a depoliticised space by demonstrating a more contentious side of civil society activism'--
Includes bibliographical references (pages 201-228) and index.
Keywords: World War, 1939-1945 -- Social aspects -- Japan; War and society -- Japan -- History -- 20th century; Collective memory -- Japan; Nationalism and collective memory -- Japan; Civil society -- Japan